Urgency of Regulatory Priorities Watershed in Order To Conduct an Integrated Watershed Administrative Law In Indonesia - I Gusti Ayu Ketut Rachmi Handayani (International Conference On Law, Business and Governance (ICon-LBG), 2013)
Watershed destruction also triggered the destruction of the water catchment area around the peak. Has led to the destruction of Ciliwung river discharge rapidly changing. Integrated Destruction of Ciliwung watershed is one of the causes that make Jakarta will not be free from floods. Ciliwung watershed management is resource management efforts involving various parties who participate from the planning stages through to monitoring and evaluation. Classification is based on the Government Regulation No. 37 in 2012 that 8 (eight) watershed in the watershed JABODETABEK, Angke-Pesanggrahan, DAS of Krukut, DAS of Ciliwung, DAS of Buaran, DAS of Sunter, DAS of Cakung, and DAS of Cisadane and DAS of Bekasi, a restored watershed carrying capacity and categorized as Priority One. Optimization of central and local governments in order structuring regulation is needed in order to administration of law of integrated watershed management.